Antifouling Compounds from Marine Invertebrates - Qi, Shu-Hua (Mar Drugs, 2017)
In this review, a comprehensive overview about the antifouling compounds from marine invertebrates is described. In total, more than 198 antifouling compounds have been obtained from marine invertebrates, specifically, sponges, gorgonian and soft corals.